Analyse du changement politique dans la République de Djibouti de 1992-2005: Contexte et Processus - Bahdon, Mohamed Abdillahi (Africana Studia, 2020)
The political change of 1990’s was imposed on the political leaders of the Republic of Djibouti. The opposition of the direction of the ex single party, the RPP, that follow other African countries, and particularly Benin and Mali, could not last a long time. The bursting of a civil war and the appearance of the political forces, armies or not, the resignation of the members of the government, a first in the short Djibouti political history, but also, the pressure of the French government on the political authorities, led to the installation of a process of change of political regime, controlled by the ex single party. The constitutional reform adopted by referendum on September 4, 1992 was not the subject of a consensus between the various political forces. The pluralist elections since December 1992 up to 2005 (presidential) did not change the local political scene significantly. The country passed from a single party to the situation of a dominant party or a single one where the opposition still does not have a parliamentary representation.